Biological Differences between Brackish and Fresh Water-Derived Aedes aegypti from Two Locations in the Jaffna Peninsula of Sri Lanka and the Implications for Arboviral Disease Transmission - Ramasamy, R.; Jude, P.J.; Veluppillai, T.; Eswaramohan, T.; Surendran, S.N. (PLOS ONE, 2014)
The mainly fresh water arboviral vector Aedes aegypti L. (Diptera: Culicidae) can also undergo pre-imaginal development in brackish water of up to 15 ppt (parts per thousand) salt in coastal areas. We investigated differences in salinity tolerance, egg laying preference, egg hatching and larval development times and resistance to common insecticides in Ae. aegypti collected from brackish and fresh water habitats in Jaffna, Sri Lanka. Brackish water-derived Ae. aegypti were more tolerant of salinity than fresh water-derived Ae. aegypti and this difference was only partly reduced after their transfer to fresh water for up to five generations. Brackish water-derived Ae. aegypti did not significantly discriminate between 10 ppt salt brackish water and fresh water for oviposition, while fresh water-derived Ae. aegypti preferred fresh water. The hatching of eggs from both brackish and fresh water-derived Ae. aegypti was less efficient and the time taken for larvae to develop into pupae was prolonged in 10 ppt salt brackish water. Ae. aegypti isolated from coastal brackish water were less resistant to the organophosphate insecticide malathion than inland fresh water Ae. aegypti. Brackish and fresh water-derived Ae. aegypti however were able to mate and produce viable offspring in the laboratory. The results suggest that development in brackish water is characterised by pertinent biological changes, and that there is restricted genetic exchange between coastal brackish and inland fresh water Ae. aegypti isolates from sites 5 km apart. The findings highlight the need for monitoring Ae. aegypti developing in coastal brackish waters and extending vector control measures to their habitats.